Correlation between Preoperative Retinometry and Postoperative Cataract Vision with Phacoemulsification and Lens Implantation in Jakarta Hospital - Kamal, Cyntia Rachmani Ferdyanti; Ardini, Witri; Erfira, Erfira; Faisal, Hiro Putra; Farida, Nida (The Avicenna Medical Journal, 2025)
Background: Cataracts, characterized by lens cloudiness, impair vision. Predicting visual outcomes after phacoemulsification with intraocular lens (IOL) implantation is crucial, and preoperative retinometry may be a valuable predictive tool. This study aimed to analyze this relationship. Methods: A cross-sectional analytical study was conducted using secondary data from 31 patients who underwent phacoemulsification with IOL at Jakarta Hospital (2020-2022). Patient characteristics (age, sex) were described. The correlation between preoperative retinometry measurements and postoperative visual acuity was analyzed using Spearman’s rank correlation test. Results: The cohort comprised 22 males and 9 females. Most male patients were aged 46–64, while most female patients were >65 years old. A statistically significant correlation was found between preoperative retinometry and postoperative visual acuity (p=0.005). The correlation strength was moderate (r=0.494), indicating that higher preoperative retinometry values predicted better postoperative visual acuity. Conclusion: Preoperative retinometry is a significant predictor of visual acuity following cataract surgery. This finding supports its clinical use for prognosticating surgical outcomes, demonstrating a direct, positive relationship between preoperative measurement and postoperative result. Keywords: Cataract, age, sex, retinometry, phacoemulsification, intraocular lens